GPCR kinases phosphorylate GPCR C-terminal peptides in a hierarchical manner - Arnelle Löbbert; Nils Lorz; Edda S. F. Matthees; Philip Rößler; Carsten Hoffmann; Alvar D. Gossert (Communications Biology)
Abstract Responses from G protein-coupled receptors (GPCRs) are downregulated in a precisely orchestrated process called desensitization. This process consists of two major steps: phosphorylation of the receptor by GPCR kinases (GRKs), predominantly on its C-terminus, and recruitment of arrestin, resulting in different signaling outcomes. Yet, it remains unclear how the phosphorylation pattern on the receptor is determined. We carried out an NMR-based study of the phosphorylation patterns generated by GRK1 and GRK2 on C-terminal peptides of selected receptors (rhodopsin for GRK1, and β1- and β2-adrenergic receptors (ARs) for GRK2). Our data reveal that the kinases are promiscuous with respect to the substrate peptide, but produce clearly defined phosphorylation patterns on each substrate. We found pronounced differences in the rates at which certain residues are phosphorylated, in particular in the PXPP motifs in rhodopsin and β1AR. These results show that GRKs produce well-defined phosphorylation patterns in absence of further modulators like the full receptor or Gβγ, and that the time profile of the phosphorylation barcode seems to be largely encoded in the minimal pair of C-terminal peptide and GRK. The data further suggest that arrestin might encounter different phosphorylation barcodes over time, hinting at the possibility of time-dependent arrestin responses.